P76 Lentiviral vectors co-expressing hepatitis B core and vFLIP induce potent CD8 T-cell and antibody responses in HLA-A2 transgenic mice. (16th November 2010) - Macdonald, D; Brindle, N; Whelan, M; Maini, M; Collins, M; Rosenberg, W
Abstract : Introduction: The failure to clear persistent Hepatitis B viral (HBV) infection is characterised by an insufficient CD8 T-cell response to several antigens including HBV core (HBc). Generating a strong T-cell response to this antigen to counter immunotolerant mechanisms in chronic HBV is an attractive therapeutic strategy. We have previously shown that lentiviral vaccines (LV) encoding antigen can generate potent CD8 and CD4 responses and these can be dramatically enhanced by co-expression of viral FLICE-like inhibitory protein (vFLIP) from Kaposi sarcoma-associated herpes virus. vFLIP is a potent stimulator of the NFKB pathway which matures and activates dendritic cells, enhancing expression of costimulatory molecules (including CD80, CD86 and ICAM1) and increasing IL-12 secretion. Aim: In this study we aimed to assess CD8 T-cell and antibody responses in HLA-A2 transgenic mice vaccinated with LV co-expressing vFLIP and HBc (A), expressing HBc alone (B) or HBc with an inactive vFLIP mutant (vFLIPa57l) (C). Method: HLA-A2 transgenic mice were vaccinated with LV 12 days before sacrifice and harvest of splenocytes. These were restimulated overnight with an HLA-A2 restricted HBc peptide (18–27) and/or overlapping HBc peptides. IFN? responses were measured by intracellular cytokine staining and by ELIspot. Antibody responses were assessed by ELISA on serum obtained at sacrifice. Results: Vaccination with LV co-expressing vFLIP and HBc (A) results in enhanced CD8-T-cell responses compared with mice vaccinated with LV expressing HBc alone (B) or HBc with an inactive vFLIP mutant (vFLIPa57l) (C). This was demonstrated on intracellular cytokine staining for IFN? of CD8+ve splenocytes re-stimulated overnight with HLA-A2 restricted peptide HBc 18–27 (A:B:C=5.35% :1.44% :0.84%). IFN? Elispot demonstrated twofold greater CD8 T-cell responses after restimulation with overlapping HBc peptides in splenocytes from mice vaccinated 12 days previously with LV co-expressing vFLIP and HBc compared with mice vaccinated with LV encoding HBc alone (p=0.006). LV expressing HBc also generated a strong antibody response comparable to vaccination with recombinant protein HBc virus-like particles (VLP). This was despite the presumed endogenous HBc antigen expression in transduced cells and no known mechanism of HBc secretion. LV encoding a mutant HBc p138g which does not multimerise into VLPs failed to raise an antibody response. Conclusion: LV encoding HBc are a potential means of generating both therapeutic CD8 T-cell and antibody responses in chronic HBV. Our data suggest that an intact VLP structure is essential for the generation of an antibody responses to HBc delivered with a lentiviral platform. We are now using this system to explore potential synergy between T-cell and B-cell responses to HBc in HBV infection.